2014
DOI: 10.2217/fon.14.10
|View full text |Cite
|
Sign up to set email alerts
|

Trabectedin for Advanced Soft Tissue Sarcomas: A Single Institution Experience

Abstract: Treatment with trabectedin is effective and well tolerated in heavily pretreated soft tissue sarcoma patients. Tapering dexamethasone courses and switching trabectedin administration to an every 4 weeks schedule effectively dealt with persistent fatigue without compromising effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
2
3
0
1
Order By: Relevance
“…Dose reductions and delays occurred more frequently in the trabectedin group than in the dacarbazine group, but were protocol-specified with the intent of minimizing trabectedin-related toxicity. These dosage adjustments were similar to those reported in other trabectedin studies, and were primarily due to transaminase elevations, neutropenia, or anemia [17, 22, 25]. The improved disease control, with equivalent reported QOL reported in the total ET43-SAR-3007 study population, suggests the importance of proper dose adjustment in patients receiving trabectedin, the majority of whom were treated as outpatients in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…Dose reductions and delays occurred more frequently in the trabectedin group than in the dacarbazine group, but were protocol-specified with the intent of minimizing trabectedin-related toxicity. These dosage adjustments were similar to those reported in other trabectedin studies, and were primarily due to transaminase elevations, neutropenia, or anemia [17, 22, 25]. The improved disease control, with equivalent reported QOL reported in the total ET43-SAR-3007 study population, suggests the importance of proper dose adjustment in patients receiving trabectedin, the majority of whom were treated as outpatients in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…Dosage and scheduling adjustments were in concordance with those reported by other studies. Dose reduction was necessary in 19.5 % of patients, which is well within the rate reported in the literature (14–48 %) [ 13 , 17 , 24 , 26 ]. As expected the primarily causes for dose reduction were either low ANC or elevated liver enzymes [ 13 , 26 ].…”
Section: Discussionsupporting
confidence: 82%
“…Trabectedin treatment in our cohort was reasonably well tolerated with an overall safety profile consistent with that of previous studies. As previously reported, the most common toxicities included self-limiting low ANC and elevated liver enzymes [ 25 , 26 ]. Neutropenia was the most common drug-related toxicity and its incidence and severity is particularly higher with the dosing schedule used by our group [ 25 ].…”
Section: Discussionmentioning
confidence: 73%
“…It should be noted that the positive results from this pivotal trial were the main reason for trabectedin approval in the United States by the US Food and Drug Administration (FDA) and in other parts of the world. Additionally, considering retrospective studies published until this time, trabectedin showed interesting efficacy in routine clinical practice . Moreover, from a medico‐economic point of view, trabectedin was found to be cost‐effective as an orphan drug for patients with short life expectancy .…”
Section: Targeting the Tumor Vasculature By Natural Compounds: Perspementioning
confidence: 99%